A lyricist's letters - Lerner, Alan Jay 1918-1986 (Oxford University Press, 2014)
As the lyricist of musicals like 'My Fair Lady' and 'Gigi', Alan Jay Lerner remains an important figure in Broadway and Hollywood history. In this collection of correspondence, author Dominic McHugh sheds new light on Lerner's working relationships with legendary figures including Rex Harrison, Richard Burton, and Frederick Loewe.